Synthesis of novel unnatural α-amino acids (UAAs) containing 7-hydroxy-2, 2-dimethyl-chroman using isoxazole as a linker. (27th August 2021) - Raghavulu, K.; Gudipati, Ramakrishna; Basavaiah, K.; Rumalla, Chidananda Swamy; Yennam, Satyanarayana; Behera, Manoranjan
Abstract : An efficient and novel method for the preparation of unnatural α-amino acids (UAAs) containing 7-hydroxy-2, 2-dimethyl-chroman via a 1, 3-di-polar-cyloaddition reaction has been described. Abstract : An efficient and novel method for the preparation of unnatural α-amino acids (UAAs) containing 7-hydroxy-2, 2-dimethyl-chroman via a 1, 3-di-polar-cyloaddition reaction has been described. Using this method, various new ethyl 2-amino-3-(3-(7-hydroxy-2, 2-dimethylchroman-6-yl)isoxazol-5-yl)propanoate derivatives have been prepared where the isoxazole ring is acting as a linker between alanine and chroman moieties. This is the first example of isoxazole-tethered 2, 2-dimethylchroman-amino acid hybrids.